Increasing the Participation of Afro-Descendants in Bank-Funded Projects in Honduras, Nicaragua and Panama - Stubbs, Josefina; Aoki, Sayo (World Bank, Washington, DC, 2012)
A World Bank's Latin America and Caribbean Region's portfolio (projects) review was carried out with the aim of , (i) analyzing the reach of the Bank's Central America Environmentally and Socially Sustainable Development (CAESSD) projects in Afro-descendant areas, and (ii) suggesting recommendations for increasing Afro-descendent participation in Bank's projects. This note, presents a brief analysis of the review and makes recommendation as fallows : use existing participatory mechanisms to ensure Afro-community participation from project design and to evaluation; considerable payoff will arise from investment in capacity building for Afro-descendants aimed at making participatory mechanisms function and sustainable; the Bank should consider expanding the project areas to reach; Afro-descendant communities. Afro-descendants should be viewed as active partners in development, and not the objects of development; integrate development plans of Afro-descendants communities and organizations at different levels (national, regional, and local) into Bank-funded projects; ensure the inclusion of Afro-descendant communities in the areas selected for projects; and finally, provide support to improve the gathering of disaggregated data for ethnic groups, including Afro-descendants.